KAJIAN FILMIS NOVEL LE COLENEL CHABERT KARYA HONORE DE BALZAC - Yeni Artanti (Jurnal Penelitian Humaniora, 2005)
Abstract This research aims at describing “ Le Colonel Chabert” as a filmic novel by using structuralism approach focusing on the intrinsic elements of the work. The elements of the story to analyze are plot, characters, background, and timing. The objectof the research is “ Le Colonel Chabert” written by Honorḗ De Balzac, last printed in 1994 bt Broadard et Taupin in Paris. The result of the research shows that  the novel constitutes a potential novel to be adapted into theatre of film.the novel isdramatic and so visual Keywords: Film, novel, “ Le Colonel Chabert, Balzac